Screening of β-glucoside kinase directed evolution library to form a sulfur-phosphorus bond - Bellag, Oualid Abdelkader; Ben Belgacem, Farah Fadwa; Noor Batcha, Ibrahim Ali; Mohd Salleh, Hamzah (Kulliyah of Engineering, International Islamic University Malaysia, 2016)
Glycoscience is a field that explores the structures and functions of glycans promising great advances in an array of applications. The objective of this research is to form a sulfur-phosphorus bond at the position 6’ of the sugar involved in many biological processes. A directed evolution strategy was adopted with error-prone PCR technique to create random mutagenesis of recombinant plasmid library of the β-glucoside kinase (βglk) recloned into a pTrcHisB plasmid and transformed into Escherichia coli. Following the creation of libraries, high throughput screening by 96-well microplate using fluorescent activated cell sorting (FACS) techniques were carried out. Positive clones were selected, sequenced for identification and enzyme expression and characterization were carried out.